The Influence of Job Characteristics and Empowerment on Employee Performance: The Role of Work Motivation as an Intervening Variable - Anggorodi, Riza Aditriawan; Hari Gursida; Widodo Sunaryo (International Journal of Management and Business Applied, 2025)
Purpose – Finding strategies and ways to improve employee performance through identification of factors that are suspected of influencing employee performance, job characteristics, empowerment and work motivation as an interverning variable in chemical industry companies. Methodology/approach – The population used came from the Production Division of a Chemical Industry Company in Bogor Regency with a total of 548 employees. The sampling technique used was purposive sampling. By using the Slovin formula, the total sample was 232 employees with a margin of error of 5%. Quantitative data were analyzed using Structural Equation Model (SEM) analysis and qualitative data were analyzed using the Delphi technique. Findings – There is a significant positive direct effect between job characteristics and empowerment on employee performance. There is a positive direct effect between job characteristics and empowerment on work motivation. There is a positive direct effect between work motivation and employee performance.